ESENSI PENGALAMAN COSPLAYER PEREMPUAN MENGHADAPI PELECEHAN SEKSUAL DI MEDIA SOSIAL INSTAGRAM - Zulfalia Az Zahra, Annisa; Sunarto, Sunarto; Hasfi, Nurul (Interaksi Online, 2024)
Cosplaying involves individuals imitating characters from comics, anime, and games. To this day, the comic, anime, and gaming communities are known to be male-dominated, which often subjects female cosplayers to various threats, including the threat of sexual harassment. These threats are experienced by female cosplayers everywhere, including on social media platforms like Instagram. This study aims to explore the essence of female cosplayers' experiences in dealing with sexual harassment on Instagram. The primary theories and concepts used in this study are the muted group theory, radical feminism, and mass communication. This is a descriptive study employing a critical phenomenology design and a critical paradigm. The research subjects are five active female cosplayers who use Instagram as a platform to publicize their cosplay activities. The results of this study highlight only a subset of female cosplayers is courageous enough to resist, with the decision to resist largely influenced by their past experiences and social interactions. Increased experience and interaction with fellow female cosplayers appear to correlate with greater confidence in resisting harassment. Conversely, limited interaction tends to leave individuals more susceptible to the influence of threats and the silencing they often endure. Female cosplayers' responses to sexual harassment are categorized into three types: direct resistance, indirect resistance, and non-resistance. The majority of participants tend to adopt indirect or non-resistant approaches, indicating that silencing is indeed prevalent, with many respondents impacted by this phenomenon. The silencing they experience encompasses not only sexual harassment but also stereotyping and emotional manipulation. Furthermore, the study underscores the significant role social media plays in perpetuating sexual harassment, as anonymity emboldens perpetrators and complicates the process of identifying them